2021
DOI: 10.2147/cmar.s324072
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-382-5p Suppresses the Expression of Farnesoid X Receptor to Promote Progression of Liver Cancer

Abstract: Background The dysregulation of microRNAs (miRNAs) and hepatotoxicity due to the aberrant accumulation of bile acids (BAs) are notorious causes that predispose an individual to the development of hepatocellular carcinoma (HCC). Farnesoid X receptor (FXR), encoded by NR1H4 gene, has been identified as a crucial BA receptor to maintain the homeostasis of BA pool and its expression is decreased in HCC. miR-382-5p plays an important role in the pathogenesis of many human mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The above results suggest that miR-382-5p expression was upregulated in both HCC tissues and cell lines, which are consistent with the miR-382-5p expression in breast cancer [ 11 ] and acute lymphocytic leukemia [ 12 ]. It is consistent with the results reported by Xiaobo NIE [ 22 ] and Juan Du [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The above results suggest that miR-382-5p expression was upregulated in both HCC tissues and cell lines, which are consistent with the miR-382-5p expression in breast cancer [ 11 ] and acute lymphocytic leukemia [ 12 ]. It is consistent with the results reported by Xiaobo NIE [ 22 ] and Juan Du [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported the role of miR-382-5p in various tumors. Xiaobo NIE [ 22 ] has reported that miR-382-5p is highly expressed in liver cancer tissues. miR-382-5p promotes the progression of HCC in vitro by suppressing FXR and could serve as a valuable therapeutic target for HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though miR-382-5p has been found in a variety of human cancers, its exact role in tumor development is unknown 13,16,33 . It was reported that miR-382-5p promoted breast cancer cell proliferation, migration, and invasion through the RERG/Ras/ERK signaling axis 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) account for 98% of the human genome and are classi ed into two types based on size and function: long non-coding RNAs and small non-coding RNAs 5,6 .MicroRNAs (miRNAs) are small non-coding RNA molecules that have 19-24 nucleotides in length and perform various regulatory functions to regulate target gene expression on post-transcriptional levels 7 .Different studies show that miRNAs have an oncogenic or tumor suppressor effect in cancer by modifying biological processes such as cell cycle, cell proliferation, metabolic activity, autophagy, invasion, and cell death 8-10 . Ho, J. Y. et al discovered that miR-382-5p had the highest expression ratio of the screened miRNAs and that miR-382-5p overexpression promoted breast cancer proliferation, migration, invasion, and metastasis 11 .In addition, miR-382-5p up-regulation was previously identi ed to play oncogenic roles by promoting the tumor cells' development in breast cancer 12 .Similarly, the alternation of miR-382-5P has been detected in Osteosarcoma (OS) 13 Hepatocellular carcinoma (HCC) 14,15 , and acute lymphocytic leukemia 16 .…”
Section: Introductionmentioning
confidence: 99%
“…NR1H4 involved in several biological processes, including lipogenesis, gluconeogenesis, ammonia detoxification, glycogen synthesis, bile acid metabolism and inflammation [7,8]. Recently, NR1H4 has been reported in multiple cancers, including colorectal cancer (CRC), hepatocellular carcinoma (HCC), non-small cell lung cancer (NSCLC), breast cancer, cholangiocarcinoma, cervical cancer [9][10][11][12][13][14]. Shan Li.…”
Section: Introductionmentioning
confidence: 99%